A Systematic Literature Review Of Religiosity On Customers' Decisions In Choosing Islamic Bank - Dita Nur Amaliatul Chusniah; Andriani Samsuri (JPS (Jurnal Perbankan Syariah), 2023)
This research aims to identify the influence of religiosity in determining customers' decisions to choose an Islamic bank using a systematic literature review (SLR) approach. The SLR stages start from identifying, assessing, and interpreting literature, resulting in 18 articles in 18 journals published in 2015-2022, indexed by SINTA, and having E-ISSN. The results of this research indicate that the influence of customer religiosity still has opportunities and challenges to be improved, as indicated by the low religiosity factors of each customer, such as the lack of religious calling that underlies attitudes and behavior, the basis for prohibiting usury and use limited to profit interests. The indicators of religiosity used to influence customers' decisions to choose an Islamic bank are the quality of Islamic products, avoiding riba transactions, the principle of profit sharing, and Islamic features. The research in the sample has a gap in results so it can become a gap for further research. The research proposals obtained in improving customer decisions are increasing religiosity, meeting customer needs, and the effectiveness of Islamic financial literacy. This research can be used as a reference for further research regarding the role of religiosity in influencing customers' decisions to choose Islamic banks.